2009
DOI: 10.1016/j.bbalip.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of long-chain polyunsaturated fatty acid (LC-PUFA) biosynthesis genes during zebrafish Danio rerio early embryogenesis

Abstract: Long-chain polyunsaturated fatty acids (LC-PUFAs) are essential in important physiological processes, many of which are particularly vital during embryonic development. This study investigated the expression of genes encoding enzymes involved in LC-PUFA biosynthesis, namely fatty acyl desaturase (Fad) and Elovl5- and Elovl2-like elongases, during early embryonic development of zebrafish. First, zebrafish elovl2 cDNA was isolated and functionally characterised in yeast, showing high specificity towards C20- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
67
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 64 publications
10
67
4
Order By: Relevance
“…A previous study demonstrated maternal transfer of elovl5, elovl2 and 5/6fad mRNA in zebrafish zygotes and a coordinated regulation of elovl2 and fad with the start of LC-PUFA biosynthesis in the embryo [51]. However, in the present study the higher levels of elovl5 in the egg may not be related with DHA synthesis to support embryogenesis due to the lack of synchrony in elovl5 and 4fad transcription.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…A previous study demonstrated maternal transfer of elovl5, elovl2 and 5/6fad mRNA in zebrafish zygotes and a coordinated regulation of elovl2 and fad with the start of LC-PUFA biosynthesis in the embryo [51]. However, in the present study the higher levels of elovl5 in the egg may not be related with DHA synthesis to support embryogenesis due to the lack of synchrony in elovl5 and 4fad transcription.…”
Section: Discussioncontrasting
confidence: 54%
“…It was suggested that an Elovl2-like enzyme, with higher substrate specificity towards C22, is required for efficient DHA synthesis from EPA via the Sprecher pathway but a gene coding for this enzyme in fish has, to date, only been shown in Atlantic salmon and zebrafish [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently with the mRNA tissue distribution data, previous studies highlighted the unusually high contents of DHA in C. estor liver, brain, and muscle, and also other tissues including gonads and adipose tissues ( 38 ). Similar tissue distribution patterns were observed in freshwater/salmonid species, including Atlantic salmon ( 14,18 ) and zebrafi sh ( 17 ), in which liver and intestine exhibited the highest expression signals of fads2 and elovl2 and elovl5 elongase genes. Marine fi sh species, including Asian sea bass, Atlantic cod, and cobia, had the highest expression levels of LC-PUFA biosynthesis genes in brain ( 15,19,21 ).…”
Section: Discussionmentioning
confidence: 48%
“…Similarly, fish Elovl5 demonstrated high activity for the elongation of C18 and C20 PUFA substrates, whereas C22 substrates were only elongated to a lesser extend (Agaba et al, 2004;Morais et al, 2009;Mohd-Yusof et al, 2010;Monroig et al, 2012b). Importantly, elongation of C22 PUFA including 22:5n-3 and 22:4n-6 in vertebrates is basically mediated by Elovl2, whose substrate chain-length specificity also includes C20, but not C18, PUFA substrates, the latter being only marginally or not elongated (Tvrdik et al, 2000;Leonard et al, 2002;Monroig et al, 2009;Morais et al, 2009). Overall it can be concluded that the O. vulgaris elongase cloned here is phenotypically an Elovl5-like elongase, but its sequence similarity to vertebrate Elovl2 suggests an interesting evolutionary scenario that is worth exploring in future investigations.…”
Section: Discussionmentioning
confidence: 99%